Refugee movements and aid responsiveness - Mathias Czaika; Amy Mayer (University of Freiburg, Department of International Economic Policy (iep), 2008)
This article analyses the impact of refugee migration movements on the long-term and short-term aid allocation decisions of bilateral donors. We distinguish between different types of forced migrants: internally displaced persons (IDPs) that stay in their country of origin, cross-border refugees that flee to neighboring countries, and asylum seekers in Western donor states. For the period 1992 to 2003, empirical evidence on 18 donor and 148 recipient countries suggests that short-term emergency aid is given to all types of refugee situations, but is predominantly directed towards the countries of origin. For the allocation of long-term development aid, donor states focus even more on the sending-countries of forced migrants; in general, they increase aid volumes only for the home countries of refugees, not for the hosting countries. This preference for the countries of origin is even stronger when these are sending-countries of asylum seekers to the Western aid-giving states.
Keywords: 330; bilateral aid allocation; refugee movements